2014
DOI: 10.5424/sjar/2014122-4694
|View full text |Cite
|
Sign up to set email alerts
|

Salinity contamination response to changes in irrigation management. Application of geochemical codes

Abstract: Salinity contamination caused by irrigation has been widely studied but the analysis of geochemical processes regarding agronomic variables has not adequately been considered yet. The research presented here analyzes the influence of changes in irrigation management on salinity contamination, through the use of geochemical modeling techniques, in an agricultural basin during the hydrological year of 2001 and within the period 2005-2008. The results indicate that the changes implemented in irrigation management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The excess of Na + and deficiency of Ca 2+ observed in the waters suggests a Na -Ca cationic exchange process that supplies Na + to water and removes Ca 2+ from it to a solid phase. This process has been previously mentioned in other geochemical studies in the zone (Causapé et al, 2004;García-Garizábal et al, 2014;Merchán et al, 2015).…”
Section: Ionic Ratiossupporting
confidence: 67%
See 1 more Smart Citation
“…The excess of Na + and deficiency of Ca 2+ observed in the waters suggests a Na -Ca cationic exchange process that supplies Na + to water and removes Ca 2+ from it to a solid phase. This process has been previously mentioned in other geochemical studies in the zone (Causapé et al, 2004;García-Garizábal et al, 2014;Merchán et al, 2015).…”
Section: Ionic Ratiossupporting
confidence: 67%
“…In this sense, Causapé et al (2004) started an investigation line based on the geochemical modeling of irrigation zones, which enabled the simulation of modernization scenarios for the Bardenas I irrigation zone and the verification of the environmental effects associated with the implementation of irrigation in Bardenas II. García-Garizábal et al (2014) also successfully employed geochemical modeling to analyze the salinity dynamics of irrigation return flows associated with changes in irrigation management at the Irrigation Community n • V at Bardenas. Merchán et al (2015) presented an initial assessment of the geochemical processes at a new irrigation zone of the Lerma basin (Fig.…”
Section: Introduction and Objectivementioning
confidence: 99%
“…Applications reported in the literature include the use of multivariate analysis to understand the main factor explaining the chemical evolution of waters in regional alluvial aquifers (Acero et al, 2013;Lorite-Herrera et al, 2008). For geochemical modeling, some examples of application are the use of inverse modeling approaches to elucidate the net geochemical reactions occurring in a water flow line from irrigation water to drainage water (Causapé et al, 2004a;García-Garizábal et al, 2014) or the use of direct modeling approaches to reproduce observed patterns in groundwater and to develop simulations in which different hypotheses can be tested (Kim et al, 2005;Stigter et al, 2006). However, both approaches are seldom applied to the same study area, which could improve the knowledge on the processes controlling the hydrological system.…”
Section: Introductionmentioning
confidence: 99%